Factors Influencing Financial Behavior in the use of E-Wallet (Gopay) Among Generation Z in the DKI Jakarta Region with Intention to use as a Mediating Variable - Alifah, Navrasty Dinda; Nasution, Ananta Hagabean (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The aim of this study is to identify the factors that influence financial behavior related to the use of the e-wallet service Gopay among Generation Z in the DKI Jakarta region, with the intention to use serving as a mediating variable. This research employs a quantitative methodology, utilizing a sample of 200 Gopay users. Data was collected through a questionnaire, and purposive sampling techniques were applied. Data analysis was conducted using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method. The findings reveal that perceived ease of use does not impact financial behavior. Conversely, perceived security and perceived usefulness significantly and positively influence financial behavior. The intention to use has a positive and significant effect on financial behavior. Perceived ease of use does not influence the intention to use, whereas perceived security and perceived usefulness significantly and positively affect the intention to use. The intention to use does not mediate the relationship between perceived ease of use and perceived usefulness with financial behavior. However, it does mediate the relationship between perceived security and financial behavior.